Peer Feedback in Translation Training: A Quasi-Experiment in an Advanced Chinese–English Translation Course - Lin, Zhong; Song, Xinyu; Guo, Jingwen; Wang, Feng (Frontiers in Psychology, 2021)
Although research on peer review in second language teaching has elaborated from diverse perspectives in the last 3 decades, most were conducted in the context of writing classes. Little knowledge is available about peer review of advanced second language learners in other language abilities, such as translation. To fill this gap, this case study explored how advanced second language learners provide feedback in a Chinese-English translation class, as well as the effectiveness of peer review in enhancing L2 learners’ translation quality. Data were collected from 30 English-major students, including their translation drafts, drafts with peer feedback, and final revised paper. Upon analysis, we found students adopted various forms of feedback. To be specific, they mainly used direct and indirect corrective feedback; metalinguistic corrective feedback was less used. Through further investigating the accuracy rate of revisions to peer feedback, we found peer review has a positive influence on improving students’ translation quality. The findings may shed light on the types of feedback adopted by students, and the practicality of peer review activity in translation education.